A quebra do monopólio nacional e o novo modelo de regulação para o setor petrolífero brasileiro (1997-2012) - Zulato, Murilo Sanchez (2013)
In this study we analyzed the process of the Brazilian monopoly breaking in the oil sector, executed amid an international context of the spread of neoliberal proposals. Thus, we examined the Brazilian political situation of the 1990s, during which the national program of privatization and structural reform of the state apparatus, gave to the private investor various national sectors, including the oil, which, since the end of 1990, witness the entry of private companies to work alongside Petrobras. In this context, the Agência Nacional do Petróleo (ANP) was created to regulate the sector. Based on the available documents, we evaluate that the performance of the Agency has, among its objectives and functions, the fulfilling of proposals positioned in line with neoliberal precepts, such as the promotion of an environment conducive to free competition and attractive to private investment. Our core objectives consisted in analyzing the process of Brazilian monopoly breaking of the oil sector, the creation and performance of the ANP, and evaluate the consequences of this process is still ongoing. Therefore, our research was conducted through the resources available for the study of History of the Present Time, as the theoretical framework developed by Edward Palmer Thompson, Eric Hobsbawm, François Bèdarida, among others. Several official documents were examined, such as federal laws, decrees and government programs, as well as economic data and analyzes from institutions associated, directly or indirectly, the sector studied. Thus, it was possible for us to discuss the new political and economic framework of the national oil sector, analyzing in a criticism way the results of its openness to private investment, which ended the state monopoly of oil activities in Brazil, which Petrobras exercised for more than 40 years.